História da União Democrática Ruralista (UDR) em Goiás: o epicentro da ação ruralista na Constituinte de 1988 - Barbosa, Mariana de Oliveira Lopes (2018)
This doctoral thesis aimed to identify the disputes and the correlation of forces involved in the debate around agrarian reform during the constitutional process of 1988, focusing on the Rural Democratic Union (UDR) in the state of Goias. In order to do so, it was necessary to analyze this particular organization regarding its past since its foundation, as well as its operation in other states of the country. In addition, having it been an organization with a strong personalistic feature, centered around the figure of Ronaldo Caiado, an investigation about him and his family in Goias was also very important. To understand the reasons behind the power of UDR in this region, it was essential to investigate the nature of local capitalism and the sociocultural relations built there, which shaped an environment favorable to this organization (where it grew and had great power), and also conducive to social movements struggling for land, more specifically the group connected to the Catholic church - which supported many movements: The Pastoral Commission of Land.